Islamophobia in visual media: Analyzing anti-Islam propaganda techniques in The Kashmir Files - Kertamukti, Rama; Rezkika, Shafira Aulia (Universitas Padjadjaran, 2026)
Background: This research is motivated by the propaganda utilization on movies or films which is growing day by day from overt through documentary to covert through fiction. Movies or films were eventually used by propagandists to launch propaganda using certain techniques to influence attitudes and behaviour towards a certain person or group. Purpose: this study aims to determine how much the percentage of anti-Islam Propaganda elements applied in The Kashmir Files film. Methods: this study uses a descriptive content analysis, with a sample of The Kashmir Files film that has been determined by researchers from what scenes and dialogues contain elements of anti-Islamic propaganda that are presented in this film. Results: With the unit of analysis through the sample film The Kashmir Files, the application of anti-Islamic propaganda uses propaganda techniques of Name Calling, Transfer, Card Stacking, Appeal to Fear, Demonizing the Enemy, Repetition, and Scapegoating. These propaganda techniques show anti-Islam in the storyline clearly. The results of data analysis Card Stacking and Transfer are the most frequently used and rarely used techniques, namely 18.0% and 7.4%. Other techniques found from the results of data analysis are Name Calling (15.9%), Appeal to Fear (14.8%), Demonizing the Enemy (13.8%), Repetition (15.9%), and Scapegoating (13.8%). All the techniques used by propagandists can be categorised as propaganda that displays anti-Islamic propaganda through Islamophobia. Conclusion: This study concludes that film clearly employs multiple anti-Islam propaganda techniques, with Card Stacking and Transfer being the most dominant. The the film can be categorized as promoting Islamophobia through a systematic use of persuasive and emotive propaganda strategies. Implications: The way of delivering propaganda techniques in this film uses propaganda in verbal communication and visual communication. With the presentation of conversations or dialogues, direct reports, speeches, symbols, so that propaganda looks natural in its anti-Islamic delivery.